Pelatihan Kader Remaja, Edukasi Dan Skrining Kesehatan Siswa SMK Di Kabupaten Tangerang - Komalasari, Rita; Maulidya, Siti; Yusnita; Evry, Nur Isnaeni (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2025)
Adolescent girls have a higher risk of developing anemia due to increased iron needs during puberty and menstruation. Anemia has a bad impact on physical and cognitive health, so it can reduce the productivity and learning achievement of adolescents. The long-term impact of anemia has the potential to have a high-risk pregnancy, including an increased risk of stunting in the child born. The purpose of this community service is to provide health training for adolescent cadres, screening and health education for vocational school students in Tangerang Regency. This Community Service is in collaboration with health centers and schools in Kresek District, Tangerang Regency on August 2 and 9, 2024. Ten medical students were involved in this program from coordination with the district health office and related stakeholders to the implementation of the event. The program consisted of training for 10 vocational school youth cadres, followed by nutritional status screening activities including measuring Height, Weight, Haemoglobin, Blood Sugar, Upper Arm Circumference,, then education related to anemia in adolescents was given which was attended by 127 vocational school students. ). The results of this screening emphasize the importance of educational initiatives in improving the health of adolescents that are directed at forming healthy adolescents and reducing long-term risks, such as stunting.